2010
DOI: 10.1021/nl101140t
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanoparticle Surface Charge at the Plasma Membrane and Beyond

Abstract: Herein, we demonstrate that the surface charge of gold nanoparticles (AuNPs) plays a critical role in modulating membrane potential of different malignant and nonmalignant cell types and subsequent downstream intracellular events. The findings presented here describe a novel mechanism for cell-nanoparticle interactions and AuNP uptake: modulation of membrane potential and its effect on intracellular events. These studies will help understand the biology of cell-nanoparticle interactions and facilitate the engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
454
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 563 publications
(475 citation statements)
references
References 26 publications
20
454
1
Order By: Relevance
“…A similar effect has been reported for other cationic NPs, 43,44 and in silico analyses of the process 45,46 explain it by NP entry through nanosized holes in the plasma membrane usually connected to significant cytotoxicity.…”
Section: ■ Results and Discussionsupporting
confidence: 78%
“…A similar effect has been reported for other cationic NPs, 43,44 and in silico analyses of the process 45,46 explain it by NP entry through nanosized holes in the plasma membrane usually connected to significant cytotoxicity.…”
Section: ■ Results and Discussionsupporting
confidence: 78%
“…We observed that positively charged nanoparticles had the highest cytotoxicity which is consistent with previous reports [19,22], whereas negatively charged nanoparticles induced only marginal cell death. Thus, whilst nanoparticles potentially change the conformation of the cell membrane, resulting in a disruption of cellular processes and membrane integrity [23,24], most interactions with the cell membrane do not cause any membrane disruption or extraction of the protein from the plasmalemma, as previously observed in the case of cyclodextrins [25].…”
Section: Discussionsupporting
confidence: 92%
“…Recently, Arvizo et al [19] reported that gold nanoparticles, depending on their surface charge, caused changes in membrane potential. Nevertheless, P-gp function has repeatedly been observed to be independent of membrane potential [20].…”
Section: Discussionmentioning
confidence: 99%
“…Samples were analyzed by INAA as previously described (49), and details are provided in SI Materials and Methods.…”
mentioning
confidence: 99%